1996
DOI: 10.12968/bjon.1996.5.21.1317
|View full text |Cite
|
Sign up to set email alerts
|

Administration of PRN medication by mental health nurses

Abstract: The administration of PRN medication by mental health nurses is an important, yet poorly explored aspect of psychiatric inpatient care. An examination of nurses' reasons for administering PRN medication is essential in ensuring its appropriate and effective use. Data were gathered from the drug charts of 44 inpatients on two acute psychiatric wards. Most PRN medication was given orally and the most frequently administered drugs were procyclidine, lorazepam, ibuprofen, diazepam and droperidol. The main reason f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 6 publications
3
47
1
3
Order By: Relevance
“…Benzodiazepines were the most commonly administered class of drugs as PRNs in the present study, as is the case in most other studies [1,3,5,10,20]. The exception to this is Geffen et al, who reported that the FGA, haloperidol, was the most frequently administered PRN [2].…”
Section: Discussionsupporting
confidence: 60%
“…Benzodiazepines were the most commonly administered class of drugs as PRNs in the present study, as is the case in most other studies [1,3,5,10,20]. The exception to this is Geffen et al, who reported that the FGA, haloperidol, was the most frequently administered PRN [2].…”
Section: Discussionsupporting
confidence: 60%
“…Rock's (2000) study on the administration of intramuscular injections found that there was no lesser pain for the patient by using two needles, but argued for more research into the topic. Gray, Smedley, and Thomas (1997) did a survey in Canada among 100 patients and found out that 88% of the patients got depot injections, and that patients over 50 years old were more common to get depot injections. Besenius, Clark-Carter, and Nolan (2010) studied the health professionals' attitudes for depot injections.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Als weitere Gründe für die Verabreichung wurden mit 24 % Vermeiden von Aggression [15], mit 7 % (Landeseinrichtung) Lösen von Angstzuständen [8], mit 9 % (Landeseinrichtung) Schlaflosigkeit [9] sowie Misstrauen, Hyperaktivität, Halluzinationen und Destruktivität [13] genannt. In einer neueren Studie wurden die Medikamentengruppen der Psychopharmaka als Bedarfsmedikation sowie die Gründe für die Verabreichung aufgeführt [11]. Dieser Studie zufolge wurden 77 % der Bedarfsmedikationen oral, 5 % i. m. und 1 % i. v. verabreicht.…”
Section: Literaturrechercheunclassified
“…Andere Gründe waren Ruhelosigkeit, Einschlafstörun-gen, Spannungszustände, psychotische Symptomatik, Gewalt und Verstopfung [11]. Gray et al [11] empfahlen weitere Untersuchungen, um herauszufinden, ob die Bedarfsmedikationen auf Verlangen des Patienten nach zuvor erhobenem pflegerischen Assessment erfolgt waren. Eine jüngere australische Studie [14] kommt zu ähnlichen Ergebnissen wie Gray et al [11].…”
Section: Literaturrechercheunclassified
See 1 more Smart Citation